Theorizing 'Transitional Justice' - Hoogenboom, David Anton (2014)
Early literature in the field of transitional justice was dominated by debates over the meaning of justice, with retributivists arguing for the need for criminal prosecutions following mass human rights violations and advocates of restorative justice claiming that non-prosecutorial forms of justice like truth-telling are better suited for post-conflict societies. This debate was eventually settled, at least in the field, by a belief that post-conflict societies require both criminal prosecutions and truth-telling. More recently, the debate over justice has centred on the question of whether the field and practice of transitional justice has prioritized civil and political rights over economic and social rights. While this is a significant development in the field, it points to a more fundamental reality. Debates over justice are interminable. To try to sculpt justice to fit a preconceived definition limits its capacity to respond to the needs of survivors. This realization serves as the starting point for this project—that justice must remain open to re-interpretation for it to maintain its relevance in post-conflict societies. There is, however, a central problem in the field: Transitional justice implies a justice that is in the service of the transition. What this suggests, then, is that the debates over justice, or, the justice question, have been substantially circumscribed by the transition question, thereby limiting the possible definitions of justice. While the justice question has received a great deal of attention, this project suggests that if debates over justice are to indeed remain interminable, the more fundamental concern of the field should be the way the transition question has, in fact, shaped our theorizing about justice